OPTIMAL SITE LAYOUT SELECTION FOR PLACEMENT OF FACILITIES AND MATERIAL IN THE CONSTRUCTION PROJECT OF KUBU RAYA DISTRICT EDUCATION AND TRAINING BUILDING - Meidita, Roslia Putri; Lusiana, Lusiana; Syahrudin, Syahrudin (Jurnal Teknik Sipil, 2023)
Construction project work has several essential components: construction workers, tools, materials, and other needed facilities. The placement of tools, materials, and facilities in construction projects affects the efficiency of movement (traveling distance) and the level of worker safety (safety index). It is the background of this research aims to analyse the placement of tools, materials, and other facilities in the construction project of the Kubu Raya Regency Education and Training building. In this study, indicators to point out the placement of tools, materials, and other facilities have been optimized by using some indicators such as movement efficiency (traveling distance) and the level of worker safety (safety index). Four alternative placements were drawn up (including the existing placement in the current project), analysed, and assessed which alternative is the most optimal. The other options are selected by analysing those four alternatives using the Analytical Hierarchy Process method and evaluated by weighting ranking. The analysis results show that alternative 3 is the optimal alternative to the traveling distance and safety index indicators. Alternative 3 represents that the placement of tools, materials, and facilities on the project is carried out by conditioning the access space between facilities, which is made capacious to reduce the barriers of workers in moving from one facility to another